The Relationship between the Regional and State Functions of Dietine Assemblies during the Reign of Stanisław August Poniatowski on the Example of the Trakai and Kaunas Dietines - Jusupović, Monika (History / Istorija, 2025)
The activities of the dietines in the Polish-Lithuanian Commonwealth were related to two main functions. The first was nationwide political activity manifested mainly in the election of representatives to the central authorities. The second involved regional government (or self-government) activities related to the needs and functioning of local communities. In this article, I describe the relationship between these two functions on the example of selected Lithuanian dietines functioning during the reign of Stanisław August Poniatowski. The aim is to consider how self-governing and political functions were manifested in the activities of the assemblies and which of them was dominant. I examine this issue not only by comparing the number of different dietines, but primarily by analysing the involvement of the assemblies’ members in both indicated functions and the intensity of their activities.